2017
DOI: 10.1080/07900627.2016.1262246
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and crop diversification in the 25 de Setembro irrigation scheme, Mozambique

Abstract: b cIraD-umr G-eau/research unit on Water management, actors and uses, montpellier, france; c school of commerce, university of south australia, adelaide, australia ABSTRACTCrop diversification is one way of improving the profitability of smallscale irrigation schemes. The 25 de Setembro scheme is an ideal site to analyze diversification, as it is influenced by the markets in Maputo and South Africa. This study uses information gathered from observations, discussions with irrigators and an irrigator survey. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 2 publications
(2 reference statements)
0
22
0
1
Order By: Relevance
“…The research in the six irrigation schemes in Mozambique, Tanzania and Zimbabwe identified a range of barriers to more profitable and sustainable irrigation (de Sousa et al, 2017;Mdemu, Mziray, Bjornlund, & Kashaigili, 2017;Moyo, van Rooyen, Moyo, Chivenge, & Bjornlund, 2017). These include:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The research in the six irrigation schemes in Mozambique, Tanzania and Zimbabwe identified a range of barriers to more profitable and sustainable irrigation (de Sousa et al, 2017;Mdemu, Mziray, Bjornlund, & Kashaigili, 2017;Moyo, van Rooyen, Moyo, Chivenge, & Bjornlund, 2017). These include:…”
Section: Resultsmentioning
confidence: 99%
“…The diversity of irrigators within schemes was illustrated at the 25 Setembro in Mozambique, where seven different irrigator types with different crop diversification strategies were distinguished, their differences reflecting farmers' resource access (de Sousa et al, 2017). Most farmers in the scheme produce traditional food crops, and while there are opportunities to grow more profitable crops, few do this.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The schemes and baseline surveys are reported in detail in the three country-specific articles in this issue: for Zimbabwe by Moyo et al (2017); for Tanzania by Mdemu et al (2017); and for Mozambique by de Sousa et al (2017), summarized by Bjornlund, van Rooyen, and Stirzaker (2017).…”
Section: Implementing Agricultural Innovation Platforms In Irrigationmentioning
confidence: 99%